RELIABILITY TOPOLOGY OPTIMIZATION DESIGN OF PISTON LATTICE STRUCTURE FOR INTERNAL COMBUSTION ENGINE (MT) - CHEN JianLiang; ZHAO QingHai; LI XinQing; ZHANG HongXin (Jixie qiangdu)
A piston lattice structure design method based on reliability topology optimization is proposed for the lightweight design of internal combustion engine pistons, which is decomposed into two parts of reliability analysis and deterministic topology optimization to be solved separately. A mathematical model for the reliability topology optimization of the piston lattice structure was established considering the minimized mass as the objective function and the maximum stress as the constraint. The failure probability constraint was transformed into a reliability index constraint according to the first second-order moment method, and then the random variables were transformed into standard normal variables, and the random variables were corrected and designed for deterministic topology optimization according to the sensitivity information of the random variables relative to the performance index. Finally, a comparative study of deterministic lattice design and reliable lattice design was conducted with a certain type of engine piston as an example. The results show that compared with the deterministic design, the reliability piston lattice model has more reliable performance when considering the influence of random variables. And the mass of lattice model is reduced by 11.8% compared with the original piston model, which meets the design requirement of piston lightweighting.